2017
DOI: 10.1016/j.jdermsci.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome maturation protein POMP increases proteasome assembly and activity in psoriatic lesional skin

Abstract: Altogether these results establish a potential role for POMP and proteasome assembly in psoriasis pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…We believe that proteasome degradation is less important in the cells in which the protein is sequestered within KHGs since the proteasome is not able to access this pool. The study by Zieba et al, showing regulation of POMP expression during normal keratinocyte differentiation, is in agreement with this, indicating that proteasome functionality is the most pronounced at the early stages of this process, corresponding to basal and suprabasal epidermal layers 145 .…”
Section: Discussionsupporting
confidence: 79%
“…We believe that proteasome degradation is less important in the cells in which the protein is sequestered within KHGs since the proteasome is not able to access this pool. The study by Zieba et al, showing regulation of POMP expression during normal keratinocyte differentiation, is in agreement with this, indicating that proteasome functionality is the most pronounced at the early stages of this process, corresponding to basal and suprabasal epidermal layers 145 .…”
Section: Discussionsupporting
confidence: 79%
“…Zieba and colleagues showed that the proteasome assembly chaperone POMP (proteasome maturation protein) was upregulated in psoriatic skin, resulting in an increase of proteasome levels and activities. Silencing POMP inhibited cell proliferation and differentiation, and promoted cell apoptosis via inhibition of the proteasome assembly [ 133 ]. E3 Ligase tripartite motif-containing 21 (Trim21) belongs to the Trim protein family with E3 ligase activity.…”
Section: Factors Regulating Psoriatic Keratinocytesmentioning
confidence: 99%
“…Importantly, such containment of the protein within KHGs prevents its access to the proteasome, which is not able to sample from those insoluble organelles. The importance of UPS-mediated control over profilaggrin is also supported by the biological pattern of the proteasome expression, which functions primarily in the undifferentiated keratinocytes, corresponding to basal and suprabasal epidermal layers ( Zieba et al, 2017 ); proteasome gets disassembled in the cells at the late stages of differentiation, which results from regulation of POMP expression.…”
Section: Discussionmentioning
confidence: 99%